Output voltage control of Multi Input Boost Converter based on Proportional Integral (PI) controller - Maulana, Iqbal Dafri; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
The design and implementation of a Multi Input Boost Converter (MIBC) based on Proportional-Integral (PI) control is discussed in this study to ensure output voltage stability in the face of load variations and input source fluctuations. Two DC input sources are integrated into the system architecture to produce a larger and more consistent output voltage. An Arduino Mega 2560 is used to create the PI controller, which is programmed using MATLAB/Simulink and employs PWM signal duty cycle settings to control the MOSFET in the converter circuit. Variability in input, load, and voltage setpoint are factors that influence experimental results. By comparing experimental results with a system without control, it is proven that PI control can eliminate overshoot and voltage ripple, reduce steady-state error, and maintain the output voltage close to the reference value. Additionally, in various test configurations, the system demonstrates good stability and fast response time. Therefore, MIBC with PI control can be used to improve the efficiency and reliability of multi-input power conversion, which can be beneficial for renewable energy systems requiring a stable DC power source